Modelling of Flutter Vibration using System Dynamic Approach for Analysing Limit Cycle Oscillations / Cosmas P Pagwiwoko and Louis Jezequel - Cosmas, P Pagwiwoko; Louis, Jezequel (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The objective of this work is to investigate the dynamic behaviour of a pitch-plunge fluttering aerofoil in the presence of non-linear stiffness such as free-play mechanism. In this paper we propose to represent the problem in a system dynamic approach with a closed loop system. A transfer function for generating the aerodynamic forces based on the dynamic response of structure is constructed in the feedback loop with the aid of Pade rational function approximation. The effects of the non-linear factors therefore can be included conveniently in time domain and by using this approach the stability of limit cycle oscillations (LCO) can be analysed accurately.